2022
DOI: 10.1002/hyp.14670
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of overbank hyporheic transport and biogeochemical reactions in a compound channel

Abstract: Transverse hyporheic transport and biogeochemical reactions in a compound channel remain poorly understood. As floodplains are submerged, solutes in the surface water enter the hyporheic zone of the compound channel and react with the solutes upwelling below the floodplain. Aerobic respiration (AR) and denitrification (DN) processes in the hyporheic zone of the compound channel still need to be clarified. In this paper, a 3D hydrodynamic model coupled to a 2D groundwater flow and biogeochemical model was appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…In previous numerical studies (Trauth et al, 2014), it was discovered that the expansion of the MRTs led to a progressive improvement in the NO 3 − removal efficiency. Xiao et al (2022) found O 2 removal efficiencies first increased and then decreased with MRTs, and he considered that water packages will complete biogeochemical processes in deep groundwater outside the domain, but the MRT obtained by the model is calculated from the water column in the model area, which might substantially underestimate the true MRT of the water column. Additionally, RT distribution is equally crucial, and an extremely large MRT does not ensure that all responses will progress properly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous numerical studies (Trauth et al, 2014), it was discovered that the expansion of the MRTs led to a progressive improvement in the NO 3 − removal efficiency. Xiao et al (2022) found O 2 removal efficiencies first increased and then decreased with MRTs, and he considered that water packages will complete biogeochemical processes in deep groundwater outside the domain, but the MRT obtained by the model is calculated from the water column in the model area, which might substantially underestimate the true MRT of the water column. Additionally, RT distribution is equally crucial, and an extremely large MRT does not ensure that all responses will progress properly.…”
Section: Resultsmentioning
confidence: 99%
“…The mesh independence analysis information for the surface water model and groundwater and the validation of surface water model are available in Xiao et al (2022).…”
Section: Numerical Methodologymentioning
confidence: 99%
See 2 more Smart Citations